Stripped-envelope supernova rates and host-galaxy properties. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Graur, Or; Bianco, F. B.; Modjaz, M.; Maoz, D.; Shivvers, I.; Filippenko, A. V.; Li, W.
Abstract: The progenitors of stripped-envelope supernovae (SNe Ibc) remain to be conclsuively identified, but correlations between SN rates and host-galaxy properties can constrain progenitor models. Here, we present one result from a re-analysis of the rates from the Lick Observatory Supernova Search. Galaxies with stellar masses ≲10 10 M⊙ are less efficient at producing SNe Ibc than more massive galaxies. Any progenitor scenario must seek to explain this new observation.